PERCEIVED MAGNITUDE OF UNEMPLOYMENT: A DARK HORSE IN THE LITERATURE ON PUBLIC ATTITUDES TOWARDS GOVERNMENTAL RESPONSIBILITIES TO THE UNEMPLOYED? - Mackonytė, Greta; Lomos, Catalina; van Oorschot, Wim (Baltic Journal of Political Science, 2015)
In this article, we propose a new variable in the formation of individual attitudes towards governmental responsibilities to the unemployed – the perceived magnitude of unemployment. Our choice is based on the argument that people’s reactions are strongly influenced by subjective meanings ascribed to social realities. We apply a multilevel analysis approach and mainly use the European Social Survey (2008). Results show that the perceived magnitude of unemployment positively influences public attitudes towards governmental responsibilities to the unemployed, when corrected for a series of relevant individual and national characteristics. Moreover, of all tested measures of actual unemployment rates, only the long-term unemployment rate has a significant effect on attitudes towards governmental responsibilities to the unemployed. Interestingly, this effect is negative, which raises questions about how the social realities of unemployment translate into perceptions of unemployment.